Development of Augmented Reality (AR)–Based Time Sorting Learning Media for Students with Autism to Understand Day and Night Time Changes - Guruh Agung Setiawan; Asri Wijiastuti; Siti Masitoh (MASI Mandiri Edukasi, 2026)
Students with autism often experience difficulties in understanding and organizing time sequences, particularly in distinguishing natural time periods such as day and night. This study aimed to develop Augmented Reality (AR)–based Time Sorting learning media to improve students’ understanding of day-night concepts. The research employed a development research approach using the ADDIE model, comprising Analysis, Design, Development, Implementation, and Evaluation. Data were collected through expert validation questionnaires, classroom observations, and pre-test and post-test assessments to evaluate the validity, practicality, and effectiveness of the developed media. The results showed that the AR Time Sorting learning media were categorized as valid and highly feasible, with validity scores of 100% from media and subject matter experts. Teacher responses indicated that the media were easy to use, and students maintained focus on the AR visualizations with minimal distraction. Statistical analysis revealed a significant improvement in students’ understanding of day and night concepts, with a significance value of 0.028 (p < 0.05). These findings indicate that AR-based Time Sorting learning media are effective in improving students with autism’s understanding of day and night concepts.